Pentingnya Disiplin dalam Beribadah di Gereja Kristen Setia Indonesia Jemaat Tenggalong - Kristiani Hulu; Yosia Bello (STIKAS Santo Yohanes Salib Kalimantan Barat, 2023)
The term Discipline in worship is widely known among believers, although there are Those who disagree with the word disciplne associated with worshipful matters. Personal. Discipline in worship according to the Christian concept is God’s commandment that must be carried out by everyone who has been redeemed and saved by the Lord Jesus Christ. What are the elements of worship according to the Bible? And what are the benefits of discipline in worship Research using qualitative methods with congregational interviews. The results of the study are tru worship is service to God by offering the whole body, spirit and soul with actions and atitudes full of respect and praise, and obedience with time discipline to build good relationship with God needed discipline Is not arbitrarily keywords: spiritual discipline, personal worship.